On the Third Boundary-Value Problem for an Improperly Elliptic Equation in a Disk - Burskii, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the problem of solvability of the inhomogeneous third boundary-value problem in a bounded domain for a scalar improperly elliptic differential equation with complex coefficients and homogeneous symbol. It is shown that this problem has a unique solution in the Sobolev space over the circle for special classes of boundary data from the spaces of functions with exponentially decreasing Fourier coefficients.